2018
DOI: 10.1590/1517-869220182402180439
|View full text |Cite
|
Sign up to set email alerts
|

Distance to Fitness Zone, Use of Facilities and Physical Activity in Adults

Abstract: Introduction: The characteristics of the built environment are important predictors of physically active behavior. In this regard, the presence, availability, access to and quality of public open spaces for physical activity close to home are positively associated with their use and higher levels of physical activity in the population. Objective: To analyze the association between distance from home to outdoor fitness zones with the use of these facilities and physical activity in adults from Curitiba, Brazil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 22 publications
0
11
0
8
Order By: Relevance
“…The travel time was shortest for the respondents visiting the area most frequently and longest for those visiting the area least frequently. Existing research to date has predominantly focused on the role of park proximity for frequent park use, with findings supporting the importance of distance: the closer the distance the more frequent the recreational area visits occur [12,32,[41][42][43][44]70]. This line of research asserts that distance predicts the frequency of visits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The travel time was shortest for the respondents visiting the area most frequently and longest for those visiting the area least frequently. Existing research to date has predominantly focused on the role of park proximity for frequent park use, with findings supporting the importance of distance: the closer the distance the more frequent the recreational area visits occur [12,32,[41][42][43][44]70]. This line of research asserts that distance predicts the frequency of visits.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the distance to the site increases, the demand/desire that residents have for it decreases [39,40]. Existing research provides evidence that residential proximity to the recreational area is the strongest, if not the sole, predictor of visit frequency, with people living closer to the area making more frequent visits [12,32,[41][42][43][44].…”
Section: Travel-cost Approachmentioning
confidence: 99%
“…Attending to Mora (2012) and Mora et al (2017) study, in some cases, a 64% of the households found an OG within 500m. Silva, Fermino, Santos Lopes, Alberico & Reis (2018) found that mean distance from home to fitness zone was 2,007 meters. Most researches compare more than two OG parks to better understand the element to study (Table 5).…”
Section: Barriers and Disadvantages For Usage An Ogmentioning
confidence: 99%
“…According to Table 12, it can be seen that daily exercise recommendations are not always achieved. Regarding customer' long-term loyalty, some studies show a long period of OGs use over one year in Iepsen & Silva (2015) until 42,4% of users (Chow, 2013;Ibiapina et al,2017;Iepsen & Silva, 2015;Pinheiro & Coelho Filho, 2017;Silva, et al (2016Silva, et al ( ,2018Silva, et al ( ,2017Souza et al, 2014). Family income and time spent in the places (months) were positively associated with neighbourhood income (Souza et al, 2014).…”
Section: Time-duration Long-term Loyalty and Seasonalitymentioning
confidence: 99%
“…Apesar de frequentemente atualizados e de fácil localização, esses dados não foram obtidos especificamente com a finalidade de serem utilizados em estudos sobre atividade física e saúde. Isso implica a necessidade de filtrar as informações contidas nestes arquivos ou ainda incrementar com dados secundários 24 , como feito por Silva et al 25 que combinaram informações do uso das academias ao ar livre e prática de atividade física de adultos de Curitiba, Paraná com a distância até as estruturas. De fato, uma maior disponibilização ou cooperações técnicas possibilitaria maior acesso e compartilhamento de dados espaciais entre órgãos, instituições, institutos e universidades para agregar recursos as investigações.…”
Section: Aquisição Dos Dados Espaciaisunclassified